2005
DOI: 10.1167/iovs.04-1122
|View full text |Cite
|
Sign up to set email alerts
|

Relevance Vector Machine and Support Vector Machine Classifier Analysis of Scanning Laser Polarimetry Retinal Nerve Fiber Layer Measurements

Abstract: Results from RVM and SVM trained on SLP RNFL thickness measurements are similar and provide accurate classification of glaucomatous and healthy eyes. RVM may be preferable to SVM, because it provides a Bayesian-derived probability of glaucoma as an output. These results suggest that these machine learning classifiers show good potential for glaucoma diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Studies comparing these two technologies have demonstrated that the sensitivity and specificity of various RNFL parameters using the Cirrus OCT are excellent and equivalent to the Stratus OCT (9)(10)(11)(12)(13) . Since 1990 (Goldbaum MH, et al IOVS 1990;31; ARVO Abstract 503), machine learning classifier (MLC) techniques have been applied to optical imaging and visual function measurements to improve glaucoma detection, with results suggesting that these techniques are as good as or better than currently available methods at classifying eyes as glaucomatous or healthy (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Classifiers usually employ a form of supervised learning, where the program learns from positive and ne gative training examples, representing cases where, for example, there are signs of glaucoma on data obtained by examination of the visual field (positive examples) or not (negative examples).…”
Section: Sensitivity and Specificity Of Machine Learning Classifiers mentioning
confidence: 99%
“…Studies comparing these two technologies have demonstrated that the sensitivity and specificity of various RNFL parameters using the Cirrus OCT are excellent and equivalent to the Stratus OCT (9)(10)(11)(12)(13) . Since 1990 (Goldbaum MH, et al IOVS 1990;31; ARVO Abstract 503), machine learning classifier (MLC) techniques have been applied to optical imaging and visual function measurements to improve glaucoma detection, with results suggesting that these techniques are as good as or better than currently available methods at classifying eyes as glaucomatous or healthy (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Classifiers usually employ a form of supervised learning, where the program learns from positive and ne gative training examples, representing cases where, for example, there are signs of glaucoma on data obtained by examination of the visual field (positive examples) or not (negative examples).…”
Section: Sensitivity and Specificity Of Machine Learning Classifiers mentioning
confidence: 99%
“…The NFI is calculated using a support vector machine algorithm based on several RNFL measures and assigns a number from 0 to 100 to each eye. 15 The higher the NFI, the greater the likelihood the patient has glaucoma.…”
Section: Instrumentationmentioning
confidence: 99%
“…The NFI is calculated using a support vector machine algorithm based on several RNFL measures and assigns a number from 0 to 100 to each eye. 15 The higher the NFI, the greater the likelihood the patient has glaucoma.Confocal Scanning Laser Ophthalmoscopy-The HRT II (software version 3.0, Heidelberg Engineering, Dossenheim, Germany) was used to acquire CSLO images in the study. It uses confocal scanning laser principles to obtain a 3-dimensional topographic image of the optic nerve.…”
mentioning
confidence: 99%
“…With the advantage of handling large feature space without overfitting, SVM [36] and relevance vector machine (RVM) pioneered by Tipping [29] have shown state-of-art results in classification problems [6,29,36]. RVM is a Bayesian treatment of the sparse learning problem.…”
Section: Related Workmentioning
confidence: 99%